Multidimensional value of enterprise architectures - Rodrigues, Luís Silva (2010)
The increasing complexity of organizations and the environment around them are increasingly demanding for a better and deeper knowledge about how to organize and use IT in order to fulfil the organizations mission, strategies and goals. In the past two decades, in order to obtain a description of the current IT and business state and/or to establish the desired future state, a significant number of organizations began to build Enterprise Architectures. Despite the efforts done, the resources spent and the benefits expected practitioners and researchers recognize that it is still difficult for organizations to assess and measure the Enterprise Architecture value, given the process complexity and the nature of some value factors. In this paper a multidimensional value approach is presented, that considers four value dimensions in Enterprise Architectures value analysis: strategic value, operational value, user value and economic/financial value. © 2010 IADIS.